What is the solution to the equation 2x-4(3x+6)=-6(2x+1)-4?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

`2x-4(3x+6)=-6(2x+1)-4`

Remove bracket by multiplying;

`2x-4xx3x-24 = -6xx2x-6-4`

`2x-12x-24 = -12x-6-4`

`-10x-24 = -12x-10`

Take all x parts to one side, and put the numbers on the other side. Make sure you use the correct signs.

`-10x+12x = -10+24`

`2x = 14`

`x = 7`

The answer is x = 7.

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial